In vitro Transdermal Transport of Domperidone by Compartmental Modeling Approach - Sekar Ayu Pawestri; Akhmad Kharis Nugroho; Endang Lukitaningsih (Universitas Gadjah Mada, 2021)
Transdermal delivery can be alternatively chosen for domperidone to improve its low oral bioavailability. The development of drugs into transdermal formulation needs information about the transport mechanism of the drug. This study aimed to develop models of domperidone transdermal transport in vitro based on compartmental modeling for understanding the domperidone transport mechanism. Domperidone solution (0.5g/L in a citric buffer, pH 5) was filled into the donor compartment. A comparative study was also conducted to examine the effect of different pH on domperidone transdermal transport in pH 1 (4g/L in 0.1M HCl). The shed snake-skin and cellophane membrane were pretreated for 1h with a chemical enhancer (oleic acid in propylene glycol) and assembled between the donor and the vertical diffusion cell's receptor compartment. The receptor compartment was filled in with phosphate-buffered saline at a pH of 6.8. The permeation study was performed for 8h. Samples concentration was assayed by UV-spectrophotometry. The cumulative permeation profiles of domperidone were analyzed using WinSAAM. Three and four-compartmental models were proposed with one lag compartment. The evaluation of the appropriate number of compartments in the transport model was examined based on the visual goodness of fit (GOF) and the corrected Akaike's information criterion (AICc) values. The four-compartmental model with one lag compartment was the best model describing percutaneous domperidone transport either in pH donor of 5 or pH 1. The model indicates domperidone transport follows into two parallel routes, including a lag compartment.